Visual Analysis of Post-Stroke Cognitive Impairment Treated with Acupuncture Based on Citespace - Zuo, Yufei; Wang, Weigang; Li, Na; Liang, Xiaojuan; Nan, Ye (Journal of Contemporary Medical Practice, 2024)
Objective: To visually analyze the literature on acupuncture in the treatment of post-stroke cognitive dysfunction (PSCI), in order to further understand the development trend and future prospects in this field. Methods: The relevant literatures collected by CNKI, Weipu Chinese periodical service platform and Wanfang Data knowledge Service platform were searched and mapped with CiteSpace, and the author cooperation, institutional cooperation, keyword co-occurrence, keyword clustering and keyword emergence were analyzed. Results: A total of 387 literatures were included, with 19 core authors, 11 keyword clustering modules and 11 emergent words. Conclusion: The research in this field is still in the exploratory stage. In the future, effective research information exchange platform should be actively established among scholars, research institutions and provinces to strengthen cooperation, so as to promote the rapid development of acupuncture in the treatment of PSCI.